(3JYGdjb ef eZGRi GdhGbOis - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3eMeO Hf YeQ Hf hGbO GdSgej GdCSdej HGdhdGA, GdeOfj, CHh YHO Gddg, GdhGbOj,J (B207 (3g` s
(3ChdgG (B:s
(3gPG JYdjb ef eZGRi ef ChdgG eeG GMJGL Edjg ai JVGfja CdN s
(3LeY ajgG cKjQkG ef CNHGQ GdSQGjG hGdZRhGJs
(3hGHJOCgG HSjQI YHO Gddg GHf LMTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B95s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B40 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs